Does abortion increase women's risk for post-traumatic stress? Findings from a prospective longitudinal cohort study - M Antonia Biggs; Charles E McCulloch; Brenly Rowland; Diana G Foster (BMJ Open)
Objective To prospectively assess women's risk for post-traumatic stress disorder (PTSD) and of experiencing post-traumatic stress symptoms (PTSS) over 4 years after seeking an abortion, and to assess whether symptoms are attributed to the pregnancy, abortion or birth, or other events in women's lives.Design Prospective longitudinal cohort study which followed women from approximately 1 week after receiving or being denied an abortion (baseline), then every 6 months for 4 years (9 interview waves).Setting 30 abortion facilities located throughout the USA.Participants Among 956 women presenting for abortion care, some of whom received an abortion and some of whom were denied due to advanced gestational age; 863 women are included in the longitudinal analyses.Main outcome measures PTSS and PTSD risk were measured using the Primary Care PTSD Screen (PC-PTSD). Index pregnancy-related PTSS was measured by coding the event(s) described by women as the cause of their symptoms.Analyses We used unadjusted and adjusted logistic mixed-effects regression analyses to assess whether PTSS, PTSD risk and pregnancy-related PTSS trajectories of women obtaining abortions differed from those who were denied one.Results At baseline, 39% of participants reported any PTSS and 16% reported three or more symptoms. Among women with symptoms 1-week post-abortion seeking (n=338), 30% said their symptoms were due to experiences of sexual, physical or emotional abuse or violence; 20% attributed their symptoms to non-violent relationship issues; and 19% said they were due to the index pregnancy. Baseline levels of PTSS, PTSD risk and pregnancy-related PTSS outcomes did not differ significantly between women who received and women who were denied an abortion. PTSS, PTSD risk and pregnancy-related PTSS declined over time for all study groups.Conclusions Women who received an abortion were at no higher risk of PTSD than women denied an abortion.